Increased concentration of clusterin/apolipoprotein J (apoJ) in hyperlipemic serum is paradoxically associated with decreased apoJ content in lipoproteins. Issue 2 (August 2015) - Rull, Anna; Martínez-Bujidos, Maria; Pérez-Cuellar, Montserrat; Pérez, Antonio; Ordóñez-Llanos, Jordi; Sánchez-Quesada, José Luis
Abstract: Objective: Clusterin/apolipoprotein J (apoJ) circulates in blood in part associated to lipoproteins or in unbound form. When bound to HDL, apoJ is antiatherogenic by inhibiting endothelial cell apoptosis; thus, any factor modifying apoJ association to HDL would decrease its antiatherogenic function. However, the exact distribution of apoJ in each lipoprotein fraction, or in lipoprotein-non bound form has not been specifically investigated either in normolipemia or in dyslipemia. Methods: Basic lipid profile and apoJ concentration were determined in sera from 70 subjects, including a wide range of cholesterol and triglyceride concentrations. Lipoproteins were isolated by ultracentrifugation and their lipid and apolipoprotein composition was assessed. Results: In the overall population, serum apoJ positively associated with cholesterol, triglyceride and VLDL-C concentrations, and HDL-C and triglyceride were independent predictors of increased apoJ concentration. Approximately, 20.5% of circulating apoJ was associated with lipoproteins (18.5% HDL, 0.9% LDL and 1.1% VLDL) and 79.5% was not bound to lipoproteins. Serum apoJ concentration was higher in hypercholesterolemic (HC), hypertriglyceridemic (HTG) and combined hyperlipidemic (CHL) sera compared to normolipemic (NL) sera (HC, 98.15 ± 33.6 mg/L; HTG, 103.3 ± 36.8 mg/L; CHL, 131.7 ± 26.8 mg/L; NL, 66.7 ± 33.8 mg/L; P  < 0.001). ApoJ distribution was also altered in hyperlipidemia; approximately 30% of circulating apoJ was associated to lipoproteins in the NL group whereas this proportion rounded 15% in hyperlipidemic subjects. Conclusions: Our findings indicate that hyperlipidemia increases the concentration of apoJ in serum but, in turn, the content of lipoprotein-associated apoJ decreases. The redistribution of apoJ in hyperlipidemia could compromise the antiatherogenic properties of HDL. Highlights: Hyperlipidemia increases the concentration of apoJ in serum. In contrast, the association of apoJ to lipoproteins decreases in hyperlipidemia. ApoJ might shift from HDL to VLDL and to non-bound lipoprotein form in hyperlipidemia. The association of apoJ to lipoproteins might be modulated by apoC-III and TG content.